THE IMPACT OF A CONSUMPTIVE LIFESTYLE ON THE ECONOMIC STABILITY OF MILLENNIALS - Agus Wahyu Irawan; Misbahul Khoir (Journal of Islamic Banking, 2024)
Millennials, as a dominant demographic group in the global economy, are significantly influenced by modern consumerist tendencies. This study explores the impact of a consumptive lifestyle on the economic stability of millennials, focusing on their financial management, saving patterns, and long-term economic security. The research highlights that the pervasive influence of social media, advertising, and peer pressure has exacerbated impulsive spending habits, reducing the financial resilience of millennials. By analyzing various factors, such as income levels, debt accumulation, and investment preferences, the study uncovers the challenges faced by millennials in achieving sustainable financial growth. Furthermore, the findings emphasize the need for effective financial literacy programs to counteract the negative effects of consumerism, enabling millennials to make informed financial decisions. This study concludes by recommending practical strategies to balance lifestyle aspirations with economic stability, aiming to foster a more sustainable approach to personal finance among millennials.